Profile, quality of life and the client satisfaction of beneficiaries registered under rashtriya bal swasthya karyakram (RBSK) at an urban primary health centre, Ahmedabad: A retrospective cohort study - Rashmi Sharma; Gneyaa Bhatt; Harsh Bakshi; Divyang Oza; Roshni Dave; Azbah Pirzada; Dharati Jani; Nirav Bapat; Rajesh Mehta (Wolters Kluwer Medknow Publications, 2022)
Background: Under Rashtriya Bal Swasthya Karyakram (RBSK), children (0-18 years) are screened for a spectrum of 30 health conditions, categorized under 4D's namely defect (birth), disease (chronic), deficiency disorders, and developmental delay, and referred for treatment at higher centers. The aim of this study is to document demographic, clinical profile of children detected with any of 4D's during 2018-20 at one Urban Primary health center to assess their Quality of Life (QOL) and client satisfaction. Materials and Methods: A total of 102 children <18 years were selected as per Probability Proportionate to Size for different 4D's; within each category required participants were selected randomly. Information was gathered on designed semi-structured proforma. For QOL, customized World Health organization Quality of Life Brief (WHO-BREF) Questionnaire tool was used. Client satisfaction about the RBSK was assessed among RBSK users (N = 46) with Likert scale. Result: Out of 102 cases, 97 were covered including 8 with more than 1 type of 4Ds. Majority beneficiaries were male (53.1%), from 5 to 10 years age (43.8%), and middle social class (52%). Congenital defects (48.5%) especially heart defects were the most common followed by deficiency disorders (40.2%) mostly severe anemia and/or severe acute malnutrition. Out of 46 who availed RBSK services, 82.6% rated service as very good or good. Most children (81.7%) had good QOL. Conclusion: Most detected 4D's belonged to school going age and middle class. They rated program as very good or good. Congenital defects, specifically heart defects were the most common. Overall, most children (81.7%) had good QOL.